2021
DOI: 10.1017/s0960258521000039
|View full text |Cite|
|
Sign up to set email alerts
|

Using seed respiration as a tool for calculating optimal soaking times for ‘on-farm’ seed priming of barley (Hordeum vulgare)

Abstract: A low-cost technique named ‘on-farm’ seed priming is increasingly being recognized as an effective approach to maximize crop establishment. It consists of anaerobically soaking seeds in water before sowing resulting in rapid and uniform germination, and enhanced seedling vigour. The extent of these benefits depends on the soaking time. The current determination of optimal soaking time by germination assays and mini-plot trials is resource-intensive, as it is species/genotype-specific. This study aimed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…In the present study, the first 4 hours of soaking resulted in a significant improvement in germination speed compared to dry seed (64 percent out of total 84 percent improvement at 20°C; 51 percent out of total 69 percent improvement at 25°C). These findings are consistent with a study in which length of on-farm priming was standardized in barley seeds 14 . In this study, it was determined that the rapid boost in germination speed after a few hours of priming is mostly related to the first rapid hydration of seed tissues, whereas developmental advancement is the primary source of improvements at longer soaking times.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the first 4 hours of soaking resulted in a significant improvement in germination speed compared to dry seed (64 percent out of total 84 percent improvement at 20°C; 51 percent out of total 69 percent improvement at 25°C). These findings are consistent with a study in which length of on-farm priming was standardized in barley seeds 14 . In this study, it was determined that the rapid boost in germination speed after a few hours of priming is mostly related to the first rapid hydration of seed tissues, whereas developmental advancement is the primary source of improvements at longer soaking times.…”
Section: Discussionsupporting
confidence: 92%
“…Under all three volume treatments, about half of the water was absorbed within 8 hours. This is a feature of the phase I 'imbibition' stage and shows the fast hydration of interior seed tissues 14 . As imbibition is essentially a passive process that serves as a catalyst for the resumption of metabolic activity, the priming period must be long enough to ensure that germination processes are sufficiently advanced to allow for pre-germinative effects to take place.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have reported that seed priming-soaking seeds in water for between 10 and 24 h prior to planting leads to improvements in germination percentages and plant establishment, as well as the subsequent vigour, disease resistance and ultimately yield of crop plants in semi-arid tropical areas [1,28]. It seems plausible that improved water and carbohydrate availability during germination and seedling establishment may at least partially explain these observations [29].…”
Section: Discussionmentioning
confidence: 98%
“…Under all three volume treatments, about half of the water was absorbed within 8 hours. This is a feature of the phase I ‘imbibition’ stage and shows the fast hydration of interior seed tissues [ 21 ]. As imbibition is essentially a passive process that serves as a catalyst for the resumption of metabolic activity, the priming period must be long enough to ensure that germination processes are sufficiently advanced to allow for pre-germinative effects to take place.…”
Section: Discussionmentioning
confidence: 99%